MAINTENANCE OF TARGET REFERENCE POINTS OF PROFESSIONAL SELF- DETERMINATION OF TEACHERS AS FACTOR OF PROFESSIONAL LONGEVITY - Tikhomirov, М.Yu. (Modern Psychology, 2019)
The aim of the study is to highlight the value-sense factors that determine the continuation of teachers who have reached retirement age and professional activity. Analysis of the problem of professional longevity in socionomic professions shows the importance of a meaningful attitude of the employee to his profession in terms of professional longevity. An empirical study of teachers in the Volgograd region showed that respondents with more than 30 years of experience found such characteristics of the value-meaning sphere - a higher sense of life, preference for values self-realization as opposed to materialistic, low level of emotional burnout, high level of personal self- efficiency and a number of other, including, style features of pedagogical activity. The system of guidelines of professional self-determination of long-term teachers is revealed: the content of the teacher's work, the nature of relations in the production team, the assessment of their level of professionalism, as well as plans related to continuing the teaching. For teachers who do not plan their stay in the profession, the main targets are the financial situation, personal status and negative aspects of the current situation in the educational organization.
Keywords: targets, pedagogical activities, value-meaning sphere, values, life path, career.